An analytical study of average radiation efficiency of rotating annular plates in rotating frame. (March 2021) - Wang, Zhonglong; Jiao, Yinghou; Chen, Zhaobo; Qu, Xiuquan; Fu, Tao
Abstract: The chief objective of this present research is concerned with average sound radiation efficiency of a thin homogeneous rotating annular plate which subject to a transverse load in rotating coordinate system. The governing equation is solved by using Galerkin's Method then the radiated sound power is obtained by using Rayleigh integral and the sound radiation efficiency is accordingly derived. Sound radiation pressure and sound radiation efficiency calculation results are separately verified by experiment and boundary element method (BEM) simulation. The influences of the rotating speed, geometry parameters, material parameter and boundary conditions on the sound radiation efficiency of the plate are analyzed. Results indicate that with the increase of the rotating speed, the sound radiation efficiency tends to shift to higher frequencies. Besides, with the decrease of the thickness, the sound radiation efficiency in low frequency range will increase while in medium and high frequency range will decrease. A similar conclusion is drawn in the study of Young's modulus. Finally, the phenomenon that different boundary conditions will change the distribution of sound radiation efficiency of the annular plate is observed by studying three most representative combinations of boundary conditions including clamped-free, free-free and simply supported-free.